2022
DOI: 10.1038/s41598-022-16410-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of microsymbionts nodulating Trifolium pratense in subpolar and temperate climate regions

Abstract: Rhizobia are soil-borne bacteria forming symbiotic associations with legumes and fixing atmospheric dinitrogen. The nitrogen-fixation potential depends on the type of host plants and microsymbionts as well as environmental factors that affect the distribution of rhizobia. In this study, we compared genetic diversity of bacteria isolated from root nodules of Trifolium pratense grown in two geographical regions (Tromsø, Norway and Lublin, Poland) located in distinct climatic (subpolar and temperate) zones. To ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…However, a similarity emerged in the size of the bands produced in isolates seven, eight, and nine, which resulted in five bands (150, 200, 300, 350, and 400 bp). These results aligned with earlier findings where using RFLP-PCR identified Rhizobium by three restriction enzymes (Koziel et al, 2022). The results of the RFLP-PCR using the restriction enzyme MspI showed that the electrophoresis of the PCR products resulted in diversity in the number and size of the DNA bands.…”
Section: Rflp-pcrsupporting
confidence: 90%
See 1 more Smart Citation
“…However, a similarity emerged in the size of the bands produced in isolates seven, eight, and nine, which resulted in five bands (150, 200, 300, 350, and 400 bp). These results aligned with earlier findings where using RFLP-PCR identified Rhizobium by three restriction enzymes (Koziel et al, 2022). The results of the RFLP-PCR using the restriction enzyme MspI showed that the electrophoresis of the PCR products resulted in diversity in the number and size of the DNA bands.…”
Section: Rflp-pcrsupporting
confidence: 90%
“…However, ruling out other factors is improbable, such as geographic distance and local environmental conditions, as these may also influence the genetic diversity of bacterial strains. Previous studies suggested that environmental factors also influence the variety and composition of root bacterial groups (Koziel et al, 2022). The RFLP-PCR is an essential technique with a high discriminatory ability among the bacterial species used to diagnose and identify bacteria at the species level and not only at the genus level, as in usual diagnostic tests.…”
Section: Rflp-pcrmentioning
confidence: 99%
“…phaseoli with Phaseolus spp. plants [ 48 , 49 , 61 , 62 ]. Interestingly, the importance of EPS in an effective symbiosis of R. leguminosarum with legumes depends on the type of nodules formed by host plants.…”
Section: Symbiotic Bacteriamentioning
confidence: 99%
“…Root cells produce different exudates that can be utilized by rhizosphere microorganisms (Zhao et al, 2016; Santhanam et al, 2017; Banerjee et al, 2018). These microbes enhance plant growth by increasing the availability of nutrients, nitrogen fixation, production of phytohormones and siderophore and control many Kozieł et al, 2022). We hypothesized that because of a fungal infection, bacterial and fungal communities associated with the rhizosphere of berseem clover were changed.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have focused on how the microbial communities are influenced by host genotypes and abiotic factors such as salinity and drought (Rahal and Chekireb 2021; Youseif et al 2021; Kozieł et al, 2022). We hypothesized that because of a fungal infection, bacterial and fungal communities associated with the rhizosphere of berseem clover were changed.…”
Section: Introductionmentioning
confidence: 99%